Sandpaper Letters: An Alternative Method for Teaching the Quran to Children with Intellectual Disabilities - Dyta, Fegia Rahma; Mahdi, Arisul; Irdamurni, Irdamurni; Fakhruddin, Fathiyah Mohd; Handayani, Endang Sri (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2024)
The ability to recognize Hijaiyah letters is an important initial stage in Quranic learning for children with intellectual disabilities. This study aims to determine the effectiveness of sandpaper letters as an alternative method of Quranic learning in improving the ability to recognize Hijaiyah letters in children with mild intellectual disabilities. This study used a quantitative method with a Single Subject Research (SSR) A-B-A design. Data sources were obtained through observation, interviews, and tests of a subject with mild intellectual disabilities at a school in Indonesia. All data were analyzed using (state the analysis tool) with visual graphic analysis techniques. The results of the analysis of 13 meetings showed that the data obtained in each condition, namely at baseline (A1), was carried out in 3 meetings with scores of 35%, 35%, and 35%. During the observation of the intervention condition (B), 7 meetings were held with percentages of 50%, 60%, 75%, 80%, 95%, 95%, and 95%. Finally, observations conducted during the baseline condition (A2) were carried out in 3 sessions with percentages of 90%, 90%, and 90%. Thus, sandpaper letters are effective as an alternative for multisensory-based Quran learning for children with mild intellectual disabilities.